06. MALIGNANT SUBDURAL EFFUSION FROM DURAL METASTASES: A CASE REPORT AND REVIEW OF AVAILABLE LITERATURE. (4th August 2020) - Pascual, Juan Silvestre; Torio, John Emmanuel; Legaspi, Gerardo
Abstract: Dural metastases from a distant primary site is a relatively uncommon entity. Two complications from this that have similar imaging findings and clinical presentation are subdural hematoma and subdural effusion. Multiple cases of subdural hematoma have been reported, but only eight other cases of subdural effusion have been reported in the literature. Here we present a case of subdural effusion as a complication from dural metastasis from a sigmoid adenocarcinoma in a 43 year old female. We also review the available literature, discussing the possible patho-etiologies, clinical presentations and imaging findings, as well as outcomes. We note the high recurrence rate (seen in 66% of all reported cases, including ours) and poor prognosis (days to months) of these cases.